SMALL BOWEL IMAGING - STILL A RADIOLOGIC APPROACH? - Markova, Ingrid; Kluchova, Katerina; Zboril, Radek; Mashlan, Miroslav; Herman, Miroslav (Biomedical papers, 2010)
Background: In recent years, there has been renewed interest in small bowel imaging using a variety of radiologic or endoscopic techniques. This article gives an overview and comparison of old and new techniques used in small bowel imaging. New imaging methods as computed tomography (CT), CT enteroclysis (CTEc), CT enterography (CTEg), ultrasound (US), contrast-enhanced ultrasound (CEUS), US enteroclysis, US enterography, magnetic resonance imaging (MRI), MR enteroclysis (MREc) and MR enterography (MREg) are compared with the older techniques such as small- bowel follow- through (SBFT), conventional enteroclysis (CE) and endoscopic techniques including push enteroscopy, ezofagogastroduodenoscopy (EGD), sonde enteroscopy, ileocolonoscopy, double-balloon enteroscopy, intraoperative enteroscopy and wireless capsule enteroscopy (WCE).Methods: Systematic scan of Pubmed,Medline, Ovid, Elsevier search engines was used.. Additional information was found through the bibliographical review of relevant articles.Results: SBFT has only secondary role in small bowel imaging. US is still the method of choice in imaging for pediatric populations. US and CEUS are also accepted as a method of choice especially in inflammatory cases. CE has been replaced by new cross - sectional imaging techniques (CTEc/CTEg or MREc/MREg). CTEc combines the advantages of CT and CE. MREc combines the advantages of MRI and CE. Some authors prefer CTEg or MREg with peroral bowel preparation and they strictly avoid nasojejunal intubation under fluoroscopic control. MREc has better soft tissue contrast, showing it to be more sensitive in detecting mucosal lesions than CTEc in inflammatory diseases. CTEg/MREg are techniques preferred for patients in follow-up of the inflammatory diseases. The radiologic community is not unanimous however about their role in the imaging process. CTEc/MREc as well as CTEg/MREg are superior to endoscopic methods in the investigation of small-bowel tumors. WCE gives unparalleled imaging of the mucosal surface of the small bowel especially in the event of obscure gastrointestinal bleeding and inflammatory diseases.Conclusions: In a comparison of endoscopic and radiologic approaches, radiologic techniques are less invasive for patients, they take less time to investigate and allow imaging the entire small bowel. Some do not involve radiation exposure (US, MR). Endoscopic methods are more expensive, more invasive, need longer examination time and technical special skills but without radiation exposure. The greatest advantage of some endoscopic methods is the possibility of mucosal biopsy in one step with diagnostic examination (EGD, push enteroscopy, intraoperative enteroscopy, ileocolonoscopy).
Keywords: CT enteroclysis/MR enteroclysis/Crohn's disease/Small bowel neoplasm/Contrast- enhanced ultrasound/Super-Paramagnetic of Iron Oxides (SPIO)